RADIATION MONITORING THE INDUSTRIAL NUCLEAR EXPLOSION SITES AND EVALUATION OF THE DOSES TO THE CRITICAL GROUPS OF POPULATION - V. P. Ramzaev; A. Yu. Medvedev; V. S. Repin; M. A. Timofeeva; E. V. Khramtsov (Радиационная гигиена)
The paper outlines the key elements of the radiation monitoring system at the sites of industrial nuclear explosions in the Russian Federation. The proposed recommendations describe sampling and measurements procedures, registration of the results and their cartographic presentation. The algorithm and formulas for calculating the doses to the critical groups of population are given. The recommendations are proposed, first of all, for practical application by the regional units of the State Sanitary Inspection.